2011
DOI: 10.1161/hypertensionaha.111.173948
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hyperparathyroidism With Concurrent Primary Aldosteronism

Abstract: P rimary aldosteronism (PA) is a common cause of secondary hypertension, because it involves 11.2% of referred hypertensive patients. 1 Primary hyperparathyroidism (PPTH) is much less common, with a prevalence that, albeit imprecisely known, is probably Ͻ0.01% in unselected hypertensives. However, arterial hypertension develops in the majority (56% to 80%) of the PPTH patients, 2 which can explain why they are held to be at increased risk for cardiovascular complications and death. 3 The association of PPTH w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 35 publications
4
63
0
1
Order By: Relevance
“…Indeed, calcium sensing receptors are expressed in juxtaglomerular cells in mice [23] and rats [18]. Recent findings in humans indicate that there is a tight link between the RAAS and the parathyroid glands, suggesting that the RAAS may mediate the furosemide effect on PTH secretion [4,15,16,19,20,22,29]. In a previous experimental study, we demonstrated that administration of the calcimimetic RS568 inhibited renin secretion in rats and blunted the renin response induced by furosemide [18].…”
Section: Several Hypotheses Have Been Proposed To Explain Furosemide-mentioning
confidence: 95%
“…Indeed, calcium sensing receptors are expressed in juxtaglomerular cells in mice [23] and rats [18]. Recent findings in humans indicate that there is a tight link between the RAAS and the parathyroid glands, suggesting that the RAAS may mediate the furosemide effect on PTH secretion [4,15,16,19,20,22,29]. In a previous experimental study, we demonstrated that administration of the calcimimetic RS568 inhibited renin secretion in rats and blunted the renin response induced by furosemide [18].…”
Section: Several Hypotheses Have Been Proposed To Explain Furosemide-mentioning
confidence: 95%
“…Moreover, these researchers demonstrated the expression of the mineral corticoid receptors (MR) in both PTH secreting adenoma and in parathyroid tissue [11], and the MR was predominantly located in the nucleus of the parathyroid cells, indicating that aldosterone participate in a “tonic” regulation of PTH synthesis and secretion. Finally, Tomaschitz et al [7] showed that patients with PA are with secondary hyperparathyroidism that can be successfully treated with either mineral corticoid receptor antagonists or adrenal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression and immunohistochemistry studies show PTH receptors in APAs and MR receptors in parathyroid cells. The significance of experimental studies demonstrating the expression of the PTH receptor in the cytoplasm of APA cells lies in the hypothesis that PTH may directly influence the synthesis of aldosterone and thus provide a pathway to describe the persistent state of hyperaldosteronism and hypertension in similar cases 8. The mechanism driving persistent hyperaldosteronism is an area of uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of PA in this case is on the basis of resistant hypertension without evidence of hypokalaemia or adrenal incidentaloma. Of interest, in a study of hypertensive patients, hypokalaemia was observed in 48% of patients with APA and only 17% of those with IHA 8. It is widely accepted that hypokalaemia is not a required diagnostic criteria of PA, but the distinction between IHA from low-renin primary (essential) hypertension remains an area of debate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation